2020
DOI: 10.3390/molecules25132979
|View full text |Cite
|
Sign up to set email alerts
|

Novel South African Rare Actinomycete Kribbella speibonae Strain SK5: A Prolific Producer of Hydroxamate Siderophores Including New Dehydroxylated Congeners

Abstract: In this paper, we report on the chemistry of the rare South African Actinomycete Kribbella speibonae strain SK5, a prolific producer of hydroxamate siderophores and their congeners. Two new analogues, dehydroxylated desferrioxamines, speibonoxamine 1 and desoxy-desferrioxamine D1 2, have been isolated, together with four known hydroxamates, desferrioxamine D1 3, desferrioxamine B 4, desoxy-nocardamine 5 and nocardamine 6, and a diketopiperazine (DKP) 7. The structures of 1–7 were characterized by the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…In this study, the chemical nature of the extracellular siderophore N, N', N"triacetylfusarinine C was determined by different analyses such as 1 H NMR where the isolated compound was confirmed by comparison to previously acquired spectra of TafC and ESI-MS/MS analysis in which the chemical formula C 39 H 58 FeN 6 O 15 was consistent with the known siderophore N, N', N"-triacetylfusarinine C (TafC) and finally LC-MS/MS analysis was used to characterize the chemical structure. This study matched with Kügler et al (2020) who characterized a novel siderophore produced from the bacterium Pseudomonas species by NMR analysis, also matched with Acquah et al (2020) who show those hydroxamate siderophores produced by Actinomycete Kribbella speibonae SK5 were characterized by High Resonance Electrospray ionization-Mass spectrometry (HRESIMS) (positive mode). In addition to that, Jarmusch et al (2021) revealed that highresolution LC-MS/MS was used for the structure elucidation of hydroxamate siderophores produced from Streptomyces spp.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, the chemical nature of the extracellular siderophore N, N', N"triacetylfusarinine C was determined by different analyses such as 1 H NMR where the isolated compound was confirmed by comparison to previously acquired spectra of TafC and ESI-MS/MS analysis in which the chemical formula C 39 H 58 FeN 6 O 15 was consistent with the known siderophore N, N', N"-triacetylfusarinine C (TafC) and finally LC-MS/MS analysis was used to characterize the chemical structure. This study matched with Kügler et al (2020) who characterized a novel siderophore produced from the bacterium Pseudomonas species by NMR analysis, also matched with Acquah et al (2020) who show those hydroxamate siderophores produced by Actinomycete Kribbella speibonae SK5 were characterized by High Resonance Electrospray ionization-Mass spectrometry (HRESIMS) (positive mode). In addition to that, Jarmusch et al (2021) revealed that highresolution LC-MS/MS was used for the structure elucidation of hydroxamate siderophores produced from Streptomyces spp.…”
Section: Discussionsupporting
confidence: 79%
“…Its resistance to Hg is not included in the scientific literature, although some authors have described strains of this genus resistant to other heavy metal divalent cations like Cu, Ni, and Cd ( Chanda et al, 2017 ; Rosenfeld et al, 2018 ). Other authors describe the capacity of produce siderophores by some species ( Acquah et al, 2020 ). The presence of this bacteria in a Hg-contaminated soil and the data found on the bibliography suggests postulating that species as a good target to look for strains with possible biotechnological potential for use in soil bioremediation.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxamate siderophores have therapeutic and diagnostic importance and have demonstrated antimicrobial and antitumor activities. Furthermore, antibiotics linked to siderophores, natural conjugates named sideromycins, have shown a higher antibacterial efficacy compared to normal antibiotics due to an enhanced uptake using the siderophore-mediated iron active transport and their use has been explored in a "Trojan horse" approach to overcome bacterial resistance to antibiotics [34,35]. As metal chelators, Desferal, the brand name of desferrioxamine B, was the first antibiotic used to remove excess iron in patients suffering from iron toxicity or overload, such as in the case of β-thalassemia patients that depend on blood transfusions [36].…”
Section: Dereplication Of the Main Compounds Producedmentioning
confidence: 99%